Tuukkaq – de første år - Thonsgaard, Kirsten (Peripeti, 2019)
This article deals with the beginnings of the Tuukkaq Theatre in Denmark, focusing on the first stages in the creation of the play Inuit 1975-77 and its first performance and reception by Greenlandic audiences in Greenland on the two months´ tour in the spring of 1978. Theatre being a volatile art form I´ve also found it useful to dwell on how Inuit was televised and broadcasted by DR-TV 1977-78, as the TV-edition offers a reasonably fair impression of how the play was performed from its opening night and during the first years.